Implementasi Metode Rabbani dalam Meningkatkan Daya Ingat Santri dalam Menghafal Al Qur’an di Pondok Pesantren Tahfidz Al Qur’an Al Madinah Banjarnegara - Nandang Wicaksono; Robingun Suyud El Syam; Ngatoillah linnaja (Pusat Riset dan Inovasi Nasional, 2023)
This article aims to find out the implementation of the Rabbani method in improving the memory of students in memorizing the Qur'an at the Tahfidz Al Qur'an Islamic Boarding School Al Madinah Banjarnegara. This research is a qualitative descriptive approach, where data is obtained through observation, interviews, and documentation. The main subjects of the research include the kiai and ustadz who support tahfidz Al-Qur'an, analyzed through data reduction, data presentation, and verification. The results of the study show: that the implementation of the Rabbani method at the Al Madinah Islamic boarding school is very suitable for students because it has the advantage of not only memorizing the verses of the Al-Qur'an, but being able to know the location of the number and position of the memorized verse. Implementation of more specific research on knowing the location of the memorized verse numbers and positions, further research is needed. Research contributes to Islamic education, especially the strategy of memorizing the Qur'an.